ANALISIS PENDAPATAN POLA USAHATANI BERBASIS TANAMAN PANGAN DAN PETERNAKAN DI KABUPATEN GROBOGAN - Siti Rohmatin Wisudawati; Mukson Mukson; Wiludjeng Roessali (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
This study aimed to analyze income in food crop and livestock based farming system, and to analyze factors influencing farmer’s income in Grobogan district. This research was conducted in November to December 2018 in Pulokulon District and Toroh District, Grobogan Regency. The research used survey method by direct interview with a questionnaire guide. Quota sampling was used to determine the number of samples. The number of farmer respondents as samples was 70 people selected by Snowball sampling method. The results of this research shows that there were two patterns of farming system carried out by the respondents including rice-corn-soybean-beef cattle (pattern I) and rice-corn-rice-beef cattle (pattern II). The average income of the farmers with the pattern I was IDR 16,596,380/year under a business scale of 0.32 ha, while the average income in pattern II was lower which was IDR 16,222,162/year under a business scale of 0.30 ha. Based on Independent Sample t-test there was no significant difference between the incomes in pattern I and pattern II. Both the pattern I and the pattern II had the same R/C Ratio of 1.54. The profitability was 53.91% under the pattern I and 53.74% under the pattern II. The two farming patterns are feasible because their R/C Ratio > 1 and profitability higher than bank loan interest rate. Keywords: Food Crop, Income, Livestock, Profitability, and R/C Ratio.